Nal‐IRI+5‐FU/LV versus 5‐FU/LV in post‐gemcitabine metastatic pancreatic cancer: Randomized phase 2 trial in Japanese patients. (25th October 2020) - Ueno, Makoto; Nakamori, Shoji; Sugimori, Kazuya; Kanai, Masashi; Ikeda, Masafumi; Ozaka, Masato; Furukawa, Masayuki; Okusaka, Takuji; Kawabe, Ken; Furuse, Junji; Komatsu, Yoshito; Ishii, Hiroshi; et al.
Abstract: Background: In the NAPOLI‐1 phase 3 trial, liposomal irinotecan (nal‐IRI) +5‐fluorouracil/leucovorin (5‐FU/LV) significantly increased mPFS versus 5‐FU/LV (3.1 vs. 1.5 months [unstratified HR = 0.56, p  = 0.0001]) in patients with mPAC that progressed on prior gemcitabine‐based therapy. This randomized phase 2 trial evaluated nal‐IRI+5‐FU/LV tolerability (Part 1), safety, and efficacy (Part 2; outcomes reported here) in Japanese patients with mPAC that progressed on gemcitabine‐based therapy. Methods: Patients were randomized 1:1 and stratified by KPS (70 and 80 vs. ≥90) and baseline albumin (≥4.0 g/dl vs. <4.0 g/dl). Primary endpoint was PFS; secondary endpoints were ORR, DCR, OS, TTF, CA19‐9 response, and QoL. The ITT population comprised all randomized patients. Results: Patient characteristics differed between nal‐IRI+5‐FU/LV (n = 40) and 5‐FU/LV (n = 39) arms, including baseline hepatic lesions (63% vs. 51%), stage IV disease at diagnosis (78% vs. 51%), and post‐study anticancer therapy (55% vs. 72%). Investigator‐assessed mPFS increase with nal‐IRI+5‐FU/LV was clinically meaningful and statistically significant versus 5‐FU/LV (2.7 vs. 1.5 months, HR = 0.60). Independently assessed mPFS showed similar trends (1.7 vs. 1.6 months, HR = 0.79). mOS was 6.3 months with nal‐IRI+5‐FU/LV and not reached with 5‐FU/LV. ORR increased significantly with nal‐IRI+5‐FU/LV versus 5‐FU/LV (18% vs. 0, rate difference 17.5). Commonly reported grade ≥3 treatment‐emergent AEs were decreased neutrophil count (37% vs. 3%), decreased white blood cell count (20% vs. 0), and diarrhea (17% vs. 3%). Conclusions: In conclusion, clinically meaningful and statistically significant gains in investigator‐assessed PFS and ORR were observed with nal‐IRI+5‐FU/LV versus 5‐FU/LV in Japanese patients, with no new or unexpected safety signals. (Clinicaltrials.gov ID: NCT02697058). Abstract : The phase 3 NAPOLI‐1 trial has previously shown the efficacy of liposomal irinotecan (nal‐IRI)+5‐FU/LV in treatment of patients with metastatic pancreatic cancer that has progressed on gemcitabine‐based therapy, but did not include any Japanese patients. This randomized phase 2 trial demonstrated clinically meaningful and statistically significant gains in investigator‐assessed progression‐free survival and objective response rate with nal‐IRI+5‐FU/LV vs 5‐FU/LV in Japanese patients. No novel or unexpected safety signals were observed in this population.